Self-Regulation and Mindfulness - Gibbs, Varleisha (PESI, 2017)
Based on the latest research in neuroscience, Self-Regulation & Mindfulness provides highly practical, kid friendly lessons to teach therapists, parents, educators and children about their brain and body, so they can build the needed skills to self-regulate.